Evaluation of the impact of agricultural insurance program of the PCIC on agricultural producers in Region 2 - Vilma D. Conrado; Jocelyn Tuscano; Beatriz O\~nate; Erwin Torio; Jane Umengan; Nina Klare Paat (Philippine Institute for Development Studies (PIDS), 2017)
This study aims to evaluate the impact of agricultural insurance of the Philippine Crop Insurance Corporation (PCIC) on corn farmers in the Cagayan Valley Region, Philippines. A total of 500 corn farmers were classified into the following treatments: 250 corn farmers with insurance (118 with indemnity claims and 132 without indemnity claims) randomly taken from PCIC agricultural insurance subscribers for 2014 and 2015 matched with 250 without insurance from the Registry System for Basic Sectors in Agriculture list. These treatment groups were further divided according to farm size groups. Regression analysis was used to determine the demand on agricultural insurance and the t-test was used to test the difference on net farm income on corn production between treatment groups. The results show that the factors affecting the probability of PCIC insurance availment by corn farmers are farm size, government transfer income, adoption of hybrid variety, land tenure, and the distance of farmer to PCIC office. Farmers with crop insurance tend to have significantly higher adoption rate of hybrid variety than farmers without crop insurance. The larger the farm size, the higher the probability of getting insurance for their corn farms. Corn farmers who do not own the land they farm and those who received higher government transfers tend to have higher probability of getting agricultural insurance. Farmers with insurance with claim have significantly higher net incomes per hectare than those without insurance. When farmers were not grouped by farm size, farmers with insurance with claims have higher net incomes than farmers with insurance but without indemnity claims in 2014 and 2015. Similar result was found in large farms (greater than 1.0 ha) when farmers were grouped according to farm size. Therefore, there is significant impact of receiving indemnity claims on the net farm income of farmers in corn production. Hence, it is recommended that policies, programs, and efforts of the government and the PCIC be directed toward enhancing the factors that increase the availment of and review of indemnity coverage of agricultural insurance.
Keywords: 330; impact evaluation; agricultural insurance; corn production; Cagayan Valley Region - Philippines